Sodium ferric sulfate composite material as well as preparation method and application thereof

By uniform composite of the iron sulfate composite material prepared with eutectic solvent in sodium ion batteries and Prussian blue-like, the problem of low sodium storage performance of the positive electrode material of existing sodium ion batteries is solved, and the high specific capacity and rate performance are improved.

CN119786575AActive Publication Date: 2025-04-08SHENZHEN INST OF ADVANCED TECH

Patent Information

Application Number
CN202411990391.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have low sodium storage performance, resulting in limited efficiency in battery applications.

Method used

The two-step liquid phase method based on eutectic solvents is used to prepare sodium iron sulfate composite materials, and the sodium storage performance is improved through uniform composite with Prussian-like materials.

Benefits of technology

The high specific capacity, rate performance and cycle stability of sodium ferric sulfate material are achieved, and the performance of sodium ion batteries is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786575A_ABST
    Figure CN119786575A_ABST
Patent Text Reader

Abstract

The embodiment of the invention discloses a sodium ferric sulfate composite material as well as a preparation method and application thereof. The preparation method of the sodium ferric sulfate composite material comprises the following steps: mixing a sodium ferric sulfate preparation raw material containing a sodium source, an iron source, a sulfur source and an antioxidant with a deep eutectic solvent to obtain a mixed material I, carrying out a heating reaction to obtain a mixed material II containing sodium ferric sulfate, mixing the mixed material II with a preparation raw material of a prussian blue-like compound, and carrying out a reaction to obtain the sodium ferric sulfate composite material. The sodium ferric sulfate composite material is obtained. According to the preparation method disclosed by the invention, the sodium ferric sulfate and the prussian blue-like material can be uniformly compounded, and the sodium storage performance of the sodium ferric sulfate is effectively improved by fully utilizing the prussian blue-like material with high capacity and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and specifically relates to a sodium iron sulfate composite material and a preparation method and application thereof. Background Art

[0002] Sodium and lithium belong to the first main group elements, and the two have similar physical and chemical properties; sodium reserves are abundant (2.75% abundance in the earth's crust) and are evenly distributed, so sodium-ion batteries have gradually become the focus of competition for new energy technologies in countries around the world. In sodium-ion batteries, the development of positive electrode materials is relatively slow, and their cost accounts for more than 30% of the total cost of the battery. At present, the positive electrode materials of sodium-ion batteries mainly include layered oxides and polyanion compounds. Among them, polyanion compounds have attracted widespread attention for their high working voltage and good cycle stability. Sodium ferric sulfate, as a typical representative of polyanion compound positive electrode materials, also has the advantage of low cost of raw materials (sodium salts, iron salts, etc.). However, the large number of inactive polyanion groups in this type of material leads to a low theoretical specific capacity, which to a certain extent affects the application prospects of sodium ferric sulfate materials in batteries. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a method for preparing a sodium iron sulfate composite material, which adopts a two-step liquid phase method based on a deep eutectic solvent and a Prussian blue-like material with high capacity and high rate performance to improve the sodium storage performance of sodium iron sulfate.

[0004] The invention also provides a sodium iron sulfate composite material.

[0005] The invention also provides a positive electrode material.

[0006] The invention also provides a positive electrode.

[0007] The present invention also provides a secondary battery.

[0008] In a first aspect of the present invention, a method for preparing a sodium ferric sulfate composite material is proposed, comprising the following steps: mixing a sodium ferric sulfate preparation raw material containing a sodium source, an iron source, a sulfur source and an antioxidant with a low eutectic solvent to obtain a mixed material I, heating the mixed material II to obtain a sodium ferric sulfate-containing mixed material, and then mixing the mixed material II with a Prussian blue-like compound preparation raw material, reacting to obtain the sodium ferric sulfate composite material.

[0009] The method for preparing the sodium iron sulfate composite material according to the embodiment of the present invention has at least the following beneficial effects:

[0010] The preparation method of the sodium ferric sulfate composite material provided by the present invention includes configuring a low eutectic solvent system; fully dissolving the sodium ferric sulfate preparation raw materials sodium source, iron source, sulfur source and antioxidant into the low eutectic solvent, and performing liquid phase reaction at a certain temperature to obtain sodium ferric sulfate; then adding the preparation raw materials of the Prussian blue compound (such as transition metal salt and sodium ferrocyanide) to react, and the composite material of sodium ferric sulfate and the Prussian blue compound can be obtained. The method of the present invention mixes the preparation raw materials of the sodium ferric sulfate and the Prussian blue compound, which can make the sodium ferric sulfate and the Prussian blue-like materials more uniformly composited, and the Prussian blue-like positive electrode material is conducive to the rapid reversible deintercalation of sodium ions due to its high specific capacity and unique three-dimensional open framework structure, so that the high capacity and rate performance of the Prussian blue-like material can be fully utilized to effectively improve the sodium storage performance of the sodium ferric sulfate.

[0011] Among them, in the related art, a simple Prussian blue-like material is usually synthesized by a simple aqueous solution system precipitation method, and the prepared Prussian blue-like material contains a high content of crystal water. If sodium ferric sulfate is simply mixed with an aqueous solution system to obtain a Prussian blue-like material, the sodium ferric sulfate is easily deteriorated due to the crystal water of the Prussian blue-like material. The present invention adopts a two-step liquid phase method based on a low eutectic solvent to prepare a composite material, avoiding the problem of sodium ferric sulfate deteriorating due to the high crystal water content of the Prussian blue-like material prepared by the aqueous solution system, and can effectively compound the raw materials for preparing Prussian blue-like materials with sodium ferric sulfate, and obtain a composite material formed by sodium ferric sulfate and Prussian blue-like materials after the reaction, which can comprehensively utilize the advantages of both to obtain a composite positive electrode material with high specific capacity, rate performance and cycle stability. The sodium ferric sulfate composite material in the present invention has good uniformity. When used as a positive electrode material for a sodium ion battery, the sodium ion battery has a high specific capacity, rate performance and cycle stability.

[0012] In some embodiments of the present invention, in the preparation method, the mixed material II is cooled and then mixed with a raw material for preparing a Prussian blue-like compound to react to obtain the sodium iron sulfate composite material. In the present invention, the raw material containing a sodium source, an iron source, a sulfur source and an antioxidant is mixed with a low eutectic solvent, heated to react, then cooled, and mixed with a raw material for preparing a Prussian blue-like compound to continue reacting to obtain the sodium iron sulfate composite material.

[0013] In the present invention, a two-step liquid phase method is used to prepare a sodium ferric sulfate and Prussian blue-like composite positive electrode material in a low eutectic solvent system, wherein the liquid phase method can make the sodium ferric sulfate and the Prussian blue-like materials fully and uniformly composited, thereby being able to use the Prussian blue-like material with high capacity and rate performance to improve the sodium storage performance of sodium ferric sulfate.

[0014] In some embodiments of the present invention, the temperature after cooling in the cooling step is 20-80°C.

[0015] In some embodiments of the present invention, after the mixed material II is cooled, the reaction time after mixing with the raw materials for preparing the Prussian blue-like compound is 2 to 40 h.

[0016] In some embodiments of the present invention, the heating temperature in the heating reaction step is 80 to 300 °C.

[0017] In some embodiments of the present invention, the heating time in the heating reaction step is 2 to 40 h.

[0018] In some embodiments of the present invention, the Prussian blue-like compound includes: Na x M y Fe(CN)6, where M is a transition metal element, 0 < x < 2; 0 < y < 1. Optionally, the M is selected from at least one of Fe, Co, Ni, Mn, Cu, and Zn.

[0019] In some embodiments of the present invention, the raw materials for preparing the Prussian blue-like compound include a transition metal salt and sodium ferrocyanide.

[0020] In some embodiments of the present invention, the transition metal salt includes at least one of nickel chloride, nickel nitrate, nickel sulfate, zinc chloride, zinc nitrate, zinc sulfate, zinc acetate, ferrous chloride, ferrous nitrate, ferrous sulfate, iron acetate, cobalt chloride, cobalt nitrate, cobalt sulfate, manganese chloride, manganese nitrate, manganese sulfate, manganese acetate, copper chloride, copper nitrate, copper sulfate, and their hydrates. That is, the transition metal salt includes at least one of nickel chloride, nickel nitrate, nickel sulfate, zinc chloride, zinc nitrate, zinc sulfate, zinc acetate, ferrous chloride, ferrous nitrate, ferrous sulfate, iron acetate, cobalt chloride, cobalt nitrate, cobalt sulfate, manganese chloride, manganese nitrate, manganese sulfate, manganese acetate, copper chloride, copper nitrate, copper sulfate, nickel chloride hydrate, nickel nitrate hydrate, nickel sulfate hydrate, zinc chloride hydrate, zinc nitrate hydrate, zinc sulfate hydrate, zinc acetate hydrate, ferrous chloride hydrate, ferrous nitrate hydrate, ferrous sulfate hydrate, iron acetate hydrate, cobalt chloride hydrate, cobalt nitrate hydrate, cobalt sulfate hydrate, manganese chloride hydrate, manganese nitrate hydrate, manganese sulfate hydrate, manganese acetate hydrate, copper chloride hydrate, copper nitrate hydrate, and copper sulfate hydrate.

[0021] In some embodiments of the present invention, the molar ratio of the transition metal salt to sodium ferrocyanide is 1:(0.4 to 1.6), and can be optionally 1:(1 to 1.2).

[0022] In some embodiments of the present invention, the deep eutectic solvent includes a hydrogen bond acceptor and a hydrogen bond donor.

[0023] In some embodiments of the present invention, the hydrogen bond acceptor includes at least one of choline chloride, choline bromide, tetramethylammonium chloride, tetraethylammonium chloride, triethylmethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, benzyltrimethylammonium chloride, tetrapropylammonium bromide, tetrabutylammonium bromide, 1-ethyl-3-methylimidazole chloride, 1-butyl-3-methylimidazole chloride, tetrabutylphosphonium bromide, methyltriphenylphosphonium bromide, betaine or L-carnitine. Optionally, the hydrogen bond donor is choline chloride.

[0024] In some embodiments of the present invention, the hydrogen bond donor includes at least one of ethylene glycol, propylene glycol, butylene glycol, glycerol, sorbitol, xylitol, phenol, hydroquinone, resorcinol, 2-cresol, urea, thiourea, methylurea, 1,1-dimethylurea, 1,3-dimethylurea, succinic acid, ethanolamine, acetamide, benzamide, imidazole or indole. Optionally, the hydrogen bond donor is ethylene glycol.

[0025] In some embodiments of the present invention, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:(0.5-5), such as 1:(1-5), specifically 1:2.

[0026] In some embodiments of the present invention, the sodium source comprises at least one of a sodium salt or a hydrate of a sodium salt.

[0027] In some embodiments of the present invention, the sodium salt includes at least one of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium oxalate, sodium acetate or sodium citrate. That is, the sodium source includes at least one of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium oxalate, sodium acetate, sodium citrate, a hydrate of sodium sulfate, a hydrate of sodium bisulfate, a hydrate of sodium carbonate, a hydrate of sodium bicarbonate, a hydrate of sodium nitrate, a hydrate of sodium oxalate, a hydrate of sodium acetate and a hydrate of sodium citrate. Optionally, the sodium source is sodium sulfate or a hydrate of sodium sulfate.

[0028] In some embodiments of the present invention, the iron source includes at least one of an iron salt or a hydrate of an iron salt.

[0029] In some embodiments of the present invention, the iron salt includes at least one of ferrous sulfate, ammonium ferrous sulfate, ferrous nitrate, ferrous chloride, ferrous bromide, ferrous sulfate, ammonium ferric sulfate, ferric nitrate, ferric chloride or ammonium ferric citrate. That is, the iron source includes at least one of ferrous sulfate, ammonium ferrous sulfate, ferrous nitrate, ferrous chloride, ferrous bromide, ferrous sulfate, ammonium ferric sulfate, ferric nitrate, ferrous chloride, ammonium ferric citrate, hydrates of ferrous sulfate, hydrates of ammonium ferrous sulfate, hydrates of ferrous nitrate, hydrates of ferrous chloride, hydrates of ferrous bromide, hydrates of ferrous sulfate, hydrates of ammonium ferric sulfate, hydrates of ferrous nitrate, hydrates of ferrous chloride or hydrates of ammonium ferric citrate. Optionally, the iron source is ferrous sulfate or a hydrate of ferrous sulfate.

[0030] In some embodiments of the present invention, the sulfur source includes at least one of sulfate or a hydrate of sulfate.

[0031] In some embodiments of the present invention, the sulfate includes at least one of sodium sulfate, sodium bisulfate, ammonium bisulfate, ammonium sulfate, ferrous sulfate, ferrous ammonium sulfate, or ammonium ferric sulfate. In other words, the sulfur source includes at least one of sodium sulfate, sodium bisulfate, ammonium bisulfate, ammonium sulfate, ferrous sulfate, ferrous ammonium sulfate, ammonium ferric sulfate, sodium sulfate hydrate, sodium bisulfate hydrate, ammonium bisulfate hydrate, ammonium sulfate hydrate, ferrous sulfate hydrate, ferrous ammonium sulfate hydrate, or ammonium ferric sulfate hydrate.

[0032] In some embodiments of the present invention, at least one of the iron source or the sodium source is used as the sulfur source. Specifically, sodium sulfate is used as both the sodium source and the sulfur source, and ferrous sulfate can be used as both the iron source and the sulfur source.

[0033] In some embodiments of the present invention, the antioxidant comprises at least one of ascorbic acid, D-isoascorbic acid, citric acid, oxalic acid, sodium sulfite or propyl gallate. Optionally, the antioxidant is ascorbic acid.

[0034] In some embodiments of the present invention, the preparation method comprises the following steps:

[0035] S1, taking a hydrogen bond acceptor and a hydrogen bond donor, stirring at 60-100°C to form a transparent liquid, and obtaining a low eutectic solvent;

[0036] S2, mixing a sodium source, a sulfur source, an iron source, an antioxidant and a low eutectic solvent to obtain a mixed material I, heating the mixture to 80-300° C. and reacting for 2-40 hours to obtain a mixed material II containing sodium iron sulfate;

[0037] S3, after the mixed material II is cooled, a transition metal salt and sodium ferrocyanide are added, reacted for 2 to 40 hours, and separated to obtain the sodium ferric sulfate composite material.

[0038] In some embodiments of the present invention, the reaction temperature in step S2 is 100-240°C.

[0039] In some embodiments of the present invention, the reaction time in step S2 is 4 to 24 hours.

[0040] In some embodiments of the present invention, the temperature after cooling in step S3 is 20-80°C, such as 20-50°C.

[0041] In some embodiments of the present invention, the reaction time in step S3 is 4 to 24 hours.

[0042] In some embodiments of the present invention, the molar ratio of the transition metal salt to the sodium ions in the sodium source is (0.02-2):1, such as (0.1-0.5):1.

[0043] In some embodiments of the present invention, in step S3, the solid obtained by separation is washed and dried to obtain the sodium iron sulfate composite material. In some embodiments of the present invention, the detergent used for washing includes but is not limited to ethanol. The number of washings is not limited, such as one or more washings. In some embodiments of the present invention, the drying temperature is 60 to 150°C, and the drying time is 12 to 24 hours.

[0044] The mixed material I of the present invention contains sodium ions, iron ions, sulfate ions and antioxidants. In some embodiments of the present invention, the molar ratio of sodium element, iron element, sulfur element and antioxidant in the mixed material I is 1:(0.2-2.5):(0.8-3.0):(0.002-2.0), such as 1:(0.5-1.5):(1.0-2.0):(0.005-1.0).

[0045] In some embodiments of the present invention, the concentration of the sodium source in the mixed material I is 0.05-4.0 mol / L, such as 0.5 mol / L.

[0046] Through the above implementation, the low eutectic solvent is a special type of liquid composed of a certain stoichiometric ratio of hydrogen bond donors and hydrogen bond acceptors through strong hydrogen bonds, weak electrostatics and van der Waals force interactions. It has the advantages of easy synthesis, low price, environmental friendliness, low volatility, strong solubility, and biodegradability. It is a new generation of green solvents that can be applied to the field of nanomaterial preparation. The preparation method of the sodium ferric sulfate composite material in the present invention: using a low eutectic solvent system as a solvent to first dissolve raw materials such as sodium source, iron source, sulfur source salt and antioxidant to prepare sodium ferric sulfate, and then adding transition metal salts and sodium ferrocyanide on this basis, and continuing to react to synthesize a sodium ferric sulfate composite positive electrode material, wherein the liquid phase method based on the low eutectic solvent system can make the sodium ferric sulfate and the Prussian blue-like two materials uniformly composite, thereby making full use of the Prussian blue-like materials with high capacity and rate performance to effectively improve the sodium storage performance of sodium ferric sulfate.

[0047] In a second aspect of the present invention, a sodium iron sulfate composite material is provided, which is prepared by adopting the preparation method of the sodium iron sulfate composite material. The sodium iron sulfate composite material in the present invention has good uniformity, and when used as a positive electrode material for a sodium ion battery, the sodium ion battery has a higher specific capacity, rate performance and cycle stability.

[0048] In some embodiments of the present invention, the particle size of the sodium iron sulfate composite material is 0.2 to 20 μm, such as 1 to 10 μm.

[0049] The third aspect of the present invention provides a positive electrode material, comprising the above-mentioned sodium iron sulfate composite material.

[0050] In a fourth aspect of the present invention, a positive electrode is provided, comprising the positive electrode material or the sodium iron sulfate composite material.

[0051] In some embodiments of the present invention, the positive electrode includes a positive electrode current collector and a positive electrode active material layer.

[0052] In some embodiments of the present invention, the positive electrode active material layer includes the sodium iron sulfate composite material.

[0053] In some embodiments of the present invention, the positive electrode current collector includes, but is not limited to, one or more of aluminum, iron, tin, zinc, nickel, titanium, manganese, carbon, etc. Optionally, the positive electrode current collector is selected from at least one of aluminum foil, carbon-coated aluminum foil, iron foil, tin foil, zinc foil, nickel foil, titanium foil, and manganese foil. For example, the positive electrode current collector may be carbon-coated aluminum foil.

[0054] In a fifth aspect of the present invention, a secondary battery is provided, comprising the above-mentioned positive electrode or the above-mentioned positive electrode material or the above-mentioned sodium iron sulfate composite material.

[0055] In some embodiments of the invention, the secondary material comprises a sodium ion battery.

[0056] In some embodiments of the present invention, the secondary material further includes a negative electrode, an electrolyte and a separator.

[0057] In some embodiments of the present invention, the negative electrode includes a negative electrode current collector and a negative electrode active material layer.

[0058] In some embodiments of the present invention, the negative electrode current collector includes but is not limited to one or more of aluminum, copper, titanium, carbon, nickel, etc. Optionally, the negative electrode current collector includes a metal foil, such as one or more selected from aluminum foil, copper foil, titanium foil, stainless steel or nickel foil. For example, the negative electrode current collector can be aluminum foil.

[0059] In some embodiments of the present invention, the negative electrode active material layer includes a negative electrode active material.

[0060] In some embodiments of the present invention, the negative electrode active material includes but is not limited to one or more of conversion type and alloying type materials, organic materials, carbon-based materials, etc. For example, the negative electrode active material may be hard carbon.

[0061] In some embodiments of the present invention, the electrolyte includes an electrolyte and an electrolyte solvent.

[0062] In some embodiments of the present invention, the electrolyte comprises a sodium salt electrolyte. Optionally, the electrolyte is selected from sodium trifluoromethanesulfonate (NaCF3SO3), sodium bis(trifluoromethylsulfonyl)imide [NaN(CF3SO2)2] and its derivatives, perfluoroalkyl sodium phosphate [NaPF3(C2F5)3], sodium tetrafluorooxalate phosphate [NaPF4(C2O4)], sodium bis(oxalate borate) [NaB(C2O4)2], sodium tri(catechol) phosphate (NTBP), sulfonated polysulfonamide sodium salt, sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium tetrafluoroborate (NaBF4), sodium hexafluoroarsenate (NaAsF6), sodium nitrate (NaNO3), sodium carbonate (NaCO3), sodium chloride (NaCl), etc. One or more.

[0063] In some embodiments of the present invention, in the electrolyte solution, the concentration of the electrolyte is 0.05 to 20 mol / L, such as 0.1 to 10 mol / L, and further 1 mol / L.

[0064] In some embodiments of the present invention, the electrolyte solvent includes but is not limited to propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl formate (MF), methyl acetate (MA), N,N-dimethylacetamide (DMA), fluoroethylene carbonate (FEC), methyl propionate (MP), ethyl propionate (EP), ethyl acetate (EA), γ-butyrolactone (GBL), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), 1,3-dioxolane (DOL), 4-methyl-1,3-dioxolane (4MeDOL), dimethoxymethane (DMM), 1,2-dimethoxypropane (DMP), triethylene glycol dimethyl ether (TEGDME), dimethyl sulfone (MSM), diethylene glycol dimethyl ether (DME), vinyl sulfite (ES), propylene sulfite (PS), dimethyl sulfite (DMS), diethyl sulfite (DES), crown ether (12-crown-4), 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-propyl-3-methylimidazolium hexafluorophosphate, 1-propyl-3-methylimidazolium tetrafluoroborate, 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-1-methylimidazolium hexafluorophosphate, 1-butyl-1-methylimidazolium tetrafluoro One or more of esters, sulfones, ethers, nitriles or ionic liquid organic solvents such as borate, 1-butyl-1-methylimidazole-bis(trifluoromethylsulfonyl)imide salt, N-butyl-N-methylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, 1-butyl-1-methylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, N-methyl-N-propylpyrrolidine-bis(trifluoromethylsulfonyl)imide salt, N-methyl, propylpiperidine-bis(trifluoromethylsulfonyl)imide salt, and N-methyl, butylpiperidine-bis(trifluoromethylsulfonyl)imide salt. Optionally, the electrolyte solvent includes propylene carbonate and fluoroethylene carbonate. Further optionally, the volume ratio of the propylene carbonate and fluoroethylene carbonate is 95:5.

[0065] In some embodiments of the present invention, the separator includes, but is not limited to, one or more of an insulating porous polymer film or an inorganic porous film. Optionally, the separator can be selected from one or more of a porous polypropylene film, a porous polyethylene film, a porous composite polymer film, glass fiber paper, and a porous ceramic separator. Specifically, the separator is glass fiber paper.

[0066] In a sixth aspect of the present invention, a method for preparing a secondary battery is proposed, comprising the following steps: taking a negative electrode, an electrolyte, a separator, and a positive electrode, and assembling them to obtain the secondary battery.

[0067] In some embodiments of the present invention, the preparation method comprises the following steps: taking a negative electrode, an electrolyte, a separator, a positive electrode and a shell, and assembling them to obtain the secondary battery. Optionally, the shell can be used for battery packaging.

[0068] In some embodiments of the present invention, the preparation method further includes the step of preparing a positive electrode, specifically comprising: taking a positive electrode active material, a positive electrode conductive agent and a positive electrode binder, adding a solvent to mix to obtain a positive electrode slurry, coating it on the surface of a positive electrode current collector, drying, and forming a positive electrode active material layer on the surface of the positive electrode current collector to obtain the positive electrode. Optionally, the positive electrode current collector needs to be cleaned before coating the positive electrode slurry.

[0069] In some embodiments of the present invention, the preparation method further includes the step of preparing a negative electrode, specifically comprising: taking a negative electrode active material, a negative electrode conductive agent and a negative electrode binder, adding a solvent to mix to obtain a negative electrode slurry, coating it on the surface of a negative electrode current collector, drying, and forming a negative electrode active material layer on the surface of the negative electrode current collector to obtain the negative electrode. Optionally, the negative electrode current collector needs to be cleaned before coating the negative electrode slurry.

[0070] In some embodiments of the present invention, the preparation method further includes preparing an electrolyte, specifically comprising: mixing an electrolyte and an electrolyte solvent to obtain the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0072] Figure 1 This is a photo of the deep eutectic solvent used in Example 1 of the present invention;

[0073] Figure 2 This is the XRD pattern of the sodium iron sulfate composite material prepared in Example 1 of the present invention;

[0074] Figure 3 This is a SEM image of the sodium iron sulfate composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0075] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0076] The experimental methods in the following examples without specifying specific conditions are generally carried out according to conventional conditions in the art or conditions recommended by the manufacturers; the raw materials and reagents used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.

[0077] Example 1

[0078] This embodiment discloses a sodium iron sulfate composite material. In this embodiment, choline chloride is used as a hydrogen bond acceptor, ethylene glycol is used as a hydrogen bond donor, sodium sulfate (Na2SO4) is used as a sodium salt and a sulfate, ferrous sulfate heptahydrate (FeSO4·7H2O) is used as a ferric salt and a sulfate, ascorbic acid is used as an antioxidant, and manganese nitrate tetrahydrate (Mn(NO3)2·4H2O) is used as a transition metal salt to prepare the sodium iron sulfate composite material. Specifically, the preparation process of the sodium iron sulfate composite material includes the following steps:

[0079] (I) Weigh 2.5 mol of choline chloride and 5 mol of ethylene glycol, stir at 80°C to form a uniform transparent liquid, and then cool to room temperature to obtain a low eutectic solvent (such as Figure 1 shown).

[0080] (II) To 100 mL of the low eutectic solvent of step (I), 0.05 mol Na2SO4, 0.1 mol FeSO4·7H2O and 0.001 mol ascorbic acid were added, the mixture was fully stirred to dissolve and formed a mixed solution, and the mixture was heated to 120°C for reaction for 6 h.

[0081] (III) After cooling to room temperature, 0.02 mol Mn(NO3)2·4H2O was added, and after stirring to dissolve, 0.02 mol sodium ferrocyanide was added, and stirring was continued at room temperature for 12 h and then filtered. The solid residue was washed with ethanol several times and dried in a forced air drying oven at 80°C for 12 h to obtain a sodium iron sulfate composite material ( Figure 2 and Figure 3 (a) are XRD and SEM images of the sodium iron sulfate composite material prepared in this example.

[0082] This embodiment also discloses a positive electrode material, including the sodium iron sulfate composite material of this embodiment.

[0083] This embodiment also discloses a battery positive electrode, including the sodium iron sulfate composite material of this embodiment.

[0084] Embodiments 2 to 5

[0085] Examples 2 to 5 respectively disclose a series of sodium iron sulfate composite materials, which differ from Example 1 in that the molar ratio of choline chloride to ethylene glycol in the deep eutectic solvent is different, and the remaining experimental parameters and steps are consistent with those in Example 1. The molar ratio of choline chloride to ethylene glycol in the deep eutectic solvent in Examples 2 to 5 is shown in Table 1 below.

[0086] Examples 2 to 5 also disclose a series of battery positive electrodes, which differ from Example 1 only in that the battery positive electrodes of Examples 2 to 5 respectively include the sodium iron sulfate composite materials prepared in Examples 2 to 5.

[0087] Embodiments 6 to 25

[0088] Examples 6 to 25 respectively disclose a series of sodium iron sulfate composite materials, which differ from Example 1 in that the hydrogen bond donors in the deep eutectic solvent are different, and the remaining experimental parameters and steps are consistent with those in Example 1. The hydrogen bond donors in Examples 6 to 25 are detailed in Table 2 below.

[0089] Examples 6 to 25 also disclose a series of battery positive electrodes, which differ from Example 1 only in that the battery positive electrodes of Examples 6 to 25 respectively include the sodium iron sulfate composite materials prepared in Examples 6 to 25.

[0090] Embodiments 26 to 27

[0091] Examples 26 to 27 respectively disclose a series of sodium iron sulfate composite materials, which differ from Example 1 in that the volume of the low eutectic solvent used in step (II) is different, and the other experimental parameters and steps are consistent with those in Example 1.

[0092] The volumes of the deep eutectic solvents in Examples 26-27 are detailed in Table 3 below.

[0093] Examples 26-27 also disclose a series of battery positive electrodes, which differ from Example 1 only in that the battery positive electrodes of Examples 26-27 respectively include the sodium iron sulfate composite materials prepared in Examples 26-27.

[0094] Embodiments 28 to 32

[0095] Examples 28 to 32 respectively disclose a series of sodium iron sulfate composite materials, which differ from Example 1 in that the heat treatment reaction temperature in step (II) is different, and the other experimental parameters and steps are consistent with those in Example 1. The heat treatment reaction temperatures in Examples 28 to 32 are detailed in Table 4 below.

[0096] Examples 28 to 32 also disclose a series of battery positive electrodes, which differ from Example 1 only in that the battery positive electrodes of Examples 28 to 32 respectively include the sodium iron sulfate composite materials prepared in Examples 28 to 32.

[0097] Embodiments 33 to 45

[0098] Examples 33 to 45 respectively disclose a series of sodium iron sulfate composite materials, which differ from Example 1 in that sodium salt, and / or iron salt, and / or sulfate are used in step (II), and the remaining experimental parameters and steps are consistent with those in Example 1. The information of sodium salt, iron salt, and sulfate in Examples 33 to 45 is detailed in Table 5 below.

[0099] Examples 33 to 45 also disclose a series of battery positive electrodes, which differ from Example 1 only in that the battery positive electrodes of Examples 33 to 45 respectively include the sodium iron sulfate composite materials prepared in Examples 33 to 45.

[0100] Embodiments 46 to 50

[0101] Examples 46 to 50 respectively disclose a series of sodium iron sulfate composite materials, which differ from Example 1 in that different types of antioxidants are used in step (II), and the rest of the experimental parameters and steps are consistent with those in Example 1. The types of antioxidants in Examples 46 to 50 are detailed in Table 6 below.

[0102] Examples 46 to 50 also disclose a series of battery positive electrodes, which differ from Example 1 only in that the battery positive electrodes of Examples 46 to 50 respectively include the sodium iron sulfate composite materials prepared in Examples 46 to 50.

[0103] Examples 51 to 70

[0104] Examples 51 to 70 respectively disclose a series of sodium iron sulfate composite materials, which differ from Example 1 in that different types of transition metal salts are used in step (III), and the remaining experimental parameters and steps are consistent with those in Example 1. The antioxidants in Examples 51 to 70 are detailed in Table 7 below.

[0105] Examples 51 to 70 also disclose a series of battery positive electrodes, which differ from Example 1 only in that the battery positive electrodes of Examples 51 to 70 respectively include the sodium iron sulfate composite materials prepared in Examples 51 to 70.

[0106] Examples 71 to 140

[0107] Embodiments 71 to 140 also disclose a series of sodium ion half-cells, and the preparation process thereof specifically includes:

[0108] Positive electrode: provide the sodium iron sulfate composite material prepared in Examples 1 to 70, respectively with carbon black and polyvinylidene fluoride (mass ratio 7:2:1), add N-methylpyrrolidone to form the positive electrode active material of the half-cell of Examples 71 to 140, clean the positive electrode current collector carbon-coated aluminum foil (thickness 16 μm), and then evenly coat the positive electrode active material on the surface of the positive electrode current collector (coating thickness 200 μm), and after the positive electrode active material layer is completely dried, cut it to obtain the battery positive electrode of the required size;

[0109] Counter electrode: sodium metal sheet (thickness 400-500 μm);

[0110] Electrolyte: 1 mol / L NaClO4 / PC-FEC (95:5, v / v);

[0111] Assembling (according to the sodium ion battery assembly half-cell), including: assembling the positive electrode and the counter electrode, injecting the electrolyte to obtain a half-cell. The half-cells obtained in Examples 71 to 140 are numbered B1 to B70 respectively.

[0112] Embodiments 141 to 210

[0113] Embodiments 141 to 210 also disclose a series of sodium ion full batteries, and the preparation process thereof specifically includes:

[0114] Positive electrode: Provide the sodium iron sulfate composite material prepared in Examples 1 to 70, respectively with carbon black and polyvinylidene fluoride (mass ratio 7:2:1), add N-methylpyrrolidone to form the positive electrode active material of the full battery of Examples 141 to 210, clean the positive electrode current collector carbon-coated aluminum foil (thickness 16 μm), and then evenly coat the positive electrode active material on the surface of the positive electrode current collector (coating thickness 200 μm), and after the positive electrode active material layer is completely dried, cut it to obtain the battery positive electrode of the required size;

[0115] The electrolyte was 1 mol / L NaClO4 / PC-FEC (95:5, v / v);

[0116] The diaphragm is glass fiber paper (thickness 0.47mm); cut the diaphragm into the required size and clean it;

[0117] The negative electrode was prepared as follows: the negative electrode materials hard carbon, conductive carbon black and polyvinylidene fluoride (PVDF) were mixed evenly in a mass ratio of 8:1:1, and then N-methylpyrrolidone (NMP) solvent was added and stirred to obtain a slurry, and then the slurry was evenly coated on the surface of aluminum foil (thickness 16 μm) (coating thickness 300 μm), and then placed in a vacuum oven for drying at a baking temperature of 80°C and a baking time of 48 h;

[0118] Assembling includes: assembling using a battery negative electrode, an electrolyte, a separator and a battery positive electrode to obtain a sodium ion full battery. The sodium ion full batteries obtained in Examples 141 to 210 are numbered C1 to C70 respectively.

[0119] Comparative Example 1

[0120] This comparative example discloses a sodium iron sulfate positive electrode material prepared based on a deep eutectic solvent method, and the preparation process specifically includes:

[0121] Weigh 2.5 mol of choline chloride and 5 mol of ethylene glycol, stir at 80 ° C to form a uniform transparent liquid, and then cool to room temperature to obtain a low eutectic solvent. Add 0.05 mol of Na2SO4, 0.1 mol of FeSO4·7H2O and 0.001 mol of ascorbic acid to 100 mL of the low eutectic solvent, stir and dissolve to form a mixed solution, and heat to 120 ° C to react for 6 hours. The solid filter residue is washed with ethanol several times and dried in a forced air drying oven at 80 ° C for 12 hours to obtain the sodium iron sulfate positive electrode material.

[0122] This comparative example also discloses a sodium ion half-cell, which differs from Examples 71 to 140 only in that the sodium iron sulfate positive electrode material of this comparative example is used instead of the sodium iron sulfate composite material prepared in Examples 1 to 70. The obtained half-cell is D1.

[0123] This comparative example also discloses a sodium ion full battery, which differs from Examples 141 to 210 only in that the sodium iron sulfate positive electrode material of this comparative example is used instead of the sodium iron sulfate composite material prepared in Examples 1 to 70. The obtained full battery is E1.

[0124] Comparative Example 2

[0125] This comparative example discloses a sodium ferric sulfate positive electrode material prepared based on mixed compounding, and its preparation process specifically includes: weighing 0.05 mol Na2SO4, 0.1 mol FeSO4·7H2O and 0.001 mol ascorbic acid, ball milling for 8 hours, vacuum drying, calcining at 350°C in an argon atmosphere for 24 hours to obtain a sodium ferric sulfate material. At the same time, weighing 0.02 mol Mn(NO3)2·4H2O and dissolving it in 100 mL of water, adding 0.02 mol sodium ferrocyanide, continuing to stir at room temperature for 12 hours and then filtering, washing the solid filter residue with ethanol several times, and drying it in an 80°C blast drying oven for 12 hours to obtain a Prussian blue-like material. Finally, the obtained sodium ferric sulfate and the Prussian blue-like material are ground and mixed.

[0126] This comparative example also discloses a sodium ion half-cell, which differs from Examples 71 to 140 only in that the sodium iron sulfate positive electrode material of this comparative example is used instead of the sodium iron sulfate composite material prepared in Examples 1 to 70. The obtained half-cell is D2.

[0127] This comparative example also discloses a sodium ion full battery, which differs from Examples 141 to 210 only in that the sodium iron sulfate positive electrode material of this comparative example is used instead of the sodium iron sulfate composite material prepared in Examples 1 to 70. The obtained full battery is E2.

[0128] Test example

[0129] This test example performs performance tests on the half-cells and full-cells of each embodiment and comparative example, specifically including:

[0130] 1. The sodium ion half-cells of Examples 71 to 140 and Comparative Examples 1 to 2 were subjected to performance tests, including: specific capacity (mAh / g) at 200mA / g and 500mA / g, and capacity retention rate after 500 cycles at 500mA / g. It can be seen that: the specific capacity at 200mA / g is 96 to 127mAh / g, the specific capacity at 500mA / g is 90 to 122mAh / g, and the capacity retention rate after 500 cycles at 500mA / g is 80.3 to 92%. The sodium iron sulfate composite material prepared by the present invention has excellent capacity, rate performance and cycle stability in the sodium ion half-cell.

[0131] The specific test results are as follows:

[0132] Table 1

[0133]

[0134] Table 2

[0135]

[0136]

[0137] Table 3

[0138]

[0139] Table 4

[0140]

[0141] Table 5

[0142]

[0143]

[0144]

[0145] Table 6

[0146]

[0147]

[0148] Table 7

[0149]

[0150]

[0151] 2. The sodium ion full batteries of Examples 141 to 210 and Comparative Examples 1 to 2 were subjected to performance tests, including: specific capacity (mAh / g) at 200mA / g and 500mA / g, and capacity retention rate after 300 cycles at 500mA / g. It can be seen that: the specific capacity at 200mA / g is 92 to 121mAh / g, the specific capacity at 500mA / g is 84 to 116mAh / g, and the capacity retention rate after 300 cycles at 500mA / g is 81.5 to 92.5%. The sodium iron sulfate composite material prepared by the present invention has excellent capacity, rate performance and cycle stability in the sodium ion full battery.

[0152] The specific test results are as follows:

[0153] Table 8

[0154]

[0155] Table 9

[0156]

[0157]

[0158] Table 10

[0159]

[0160] Table 11

[0161]

[0162] Table 12

[0163]

[0164]

[0165]

[0166] Table 13

[0167]

[0168]

[0169] Table 14

[0170]

[0171]

[0172] The present invention uses a low eutectic solvent system to prepare a composite material containing sodium ferric sulfate and a Prussian blue-like material through a two-step liquid phase method, which can not only make the sodium ferric sulfate and the Prussian blue-like materials uniformly compounded, but also avoid the problem that sodium ferric sulfate is simply mixed with a Prussian blue-like material (with a high crystal water content) prepared by a conventional aqueous solution system and easily causes the sodium ferric sulfate to deteriorate, thereby making full use of the Prussian blue-like material with high capacity and rate performance to effectively improve the sodium storage performance of sodium ferric sulfate.

[0173] If there is no special explanation, the actual meaning of "about" in the present invention is that the error is allowed within the range of ±2%, for example, about 100 is actually 100±2%×100. The "normal temperature" and "room temperature" in the present invention, if there is no special explanation, are about 20 to 30°C. The "between" in the present invention includes the number itself, for example, "between 2 and 3" includes the endpoint values ​​2 and 3.

[0174] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a sodium iron sulfate composite material, characterized in that: The method comprises the following steps: mixing a sodium ferric sulfate preparation raw material containing a sodium source, an iron source, a sulfur source and an antioxidant with a low eutectic solvent to obtain a mixed material I, heating the mixed material II to obtain a sodium ferric sulfate-containing mixed material, and then mixing the mixed material II with a Prussian blue-like compound preparation raw material, reacting the mixed material II to obtain the sodium ferric sulfate composite material.

2. The method for preparing the sodium ferric sulfate composite material according to claim 1, wherein In the preparation method, the mixed material II is cooled and then mixed with a raw material for preparing a Prussian blue-like compound to react to obtain the sodium iron sulfate composite material; Preferably, the temperature after cooling in the cooling step is 20-80° C.; or / and, after the mixed material II is cooled, the reaction time after mixing with the raw material for preparing the Prussian blue-like compound is 2-40 hours.

3. The method for preparing the sodium iron sulfate composite material according to claim 1, wherein The heating temperature in the heating reaction step is 80-300° C.; or / and, the heating time in the heating reaction step is 2-40 hours; or / and, in the mixed material I, the molar ratio of sodium element, iron element, sulfur element and antioxidant is 1:(0.2-2.5):(0.8-3.0):(0.002-2.0); or / and, in the mixed material I, the concentration of the sodium source is 0.05-4.0 mol / L; Preferably, the preparation method comprises the following steps: S1, taking a hydrogen bond acceptor and a hydrogen bond donor, stirring at 60-100°C to form a transparent liquid, and obtaining a low eutectic solvent; S2, mixing a sodium source, a sulfur source, an iron source, an antioxidant and a low eutectic solvent to obtain a mixed material I, heating the mixture to 80-300° C. and reacting for 2-40 hours to obtain a mixed material II containing sodium iron sulfate; S3, after the mixed material II is cooled, a transition metal salt and sodium ferrocyanide are added, reacted for 2 to 40 hours, and separated to obtain the sodium ferric sulfate composite material.

4. The method for preparing the sodium iron sulfate composite material according to claim 1, characterized in that: The raw materials for preparing the Prussian blue-like compound include transition metal salt and sodium ferrocyanide; and / or, the transition metal salt comprises at least one of nickel chloride, nickel nitrate, nickel sulfate, zinc chloride, zinc nitrate, zinc sulfate, zinc acetate, ferrous chloride, ferrous nitrate, ferrous sulfate, ferric acetate, cobalt chloride, cobalt nitrate, cobalt sulfate, manganese chloride, manganese nitrate, manganese sulfate, manganese acetate, cupric chloride, cupric nitrate, cupric sulfate, and hydrates thereof; and / or, the molar ratio of the transition metal salt to sodium ferrocyanide is 1:(0.4-1.6); And / or, the molar ratio of the transition metal salt to the sodium ions in the sodium source is (0.02-2):

1.

5. The method for preparing the sodium iron sulfate composite material according to claim 1, characterized in that: The deep eutectic solvent comprises a hydrogen bond acceptor and a hydrogen bond donor; Preferably, the hydrogen bond acceptor comprises at least one of choline chloride, choline bromide, tetramethylammonium chloride, tetraethylammonium chloride, triethylmethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, benzyltrimethylammonium chloride, tetrapropylammonium bromide, tetrabutylammonium bromide, 1-ethyl-3-methylimidazole chloride, 1-butyl-3-methylimidazole chloride, tetrabutylphosphonium bromide, methyltriphenylphosphonium bromide, betaine or L-carnitine; Preferably, the hydrogen bond donor comprises at least one of ethylene glycol, propylene glycol, butylene glycol, glycerol, sorbitol, xylitol, phenol, hydroquinone, resorcinol, 2-cresol, urea, thiourea, methyl urea, 1,1-dimethyl urea, 1,3-dimethyl urea, succinic acid, ethanolamine, acetamide, benzamide, imidazole or indole; Preferably, the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 1:(0.5-5).

6. The method for preparing the sodium iron sulfate composite material according to claim 1, characterized in that: The sodium source includes at least one of sodium salt or sodium salt hydrate; or / and, the iron source includes at least one of iron salt or iron salt hydrate; or / and, the sulfur source includes at least one of sulfate or sulfate hydrate; or / and, the antioxidant includes at least one of ascorbic acid, D-isoascorbic acid, citric acid, oxalic acid, sodium sulfite or propyl gallate; Preferably, the sodium salt comprises at least one of sodium sulfate, sodium bisulfate, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium oxalate, sodium acetate or sodium citrate; or / and, the iron salt comprises at least one of ferrous sulfate, ammonium ferrous sulfate, ferrous nitrate, ferrous chloride, ferrous bromide, ferric sulfate, ammonium ferric sulfate, ferric nitrate, ferric chloride or ammonium ferric citrate; or / and, the sulfate comprises at least one of sodium sulfate, sodium bisulfate, ammonium bisulfate, ammonium sulfate, ferrous sulfate, ferrous ammonium sulfate or ammonium ferric sulfate.

7. A sodium iron sulfate composite material, characterized in that: The sodium iron sulfate composite material is prepared by adopting the preparation method of any one of claims 1 to 6.

8. A positive electrode material, characterized in that The invention comprises the sodium iron sulfate composite material prepared by the preparation method according to any one of claims 1 to 6 or the sodium iron sulfate composite material according to claim 7.

9. A positive electrode, characterized in that The invention comprises the sodium iron sulfate composite material obtained by the preparation method according to any one of claims 1 to 6, the sodium iron sulfate composite material according to claim 7, or the positive electrode material according to claim 8.

10. A secondary battery, characterized in that: It comprises the sodium iron sulfate composite material obtained by the preparation method according to any one of claims 1 to 6, or the sodium iron sulfate composite material according to claim 7, or the positive electrode material according to claim 8, or the positive electrode according to claim 9.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material and preparation method thereof

    CN115810752A

  • Prussian blue-like nanometer positive electrode material, preparation method thereof and sodium ion battery

    CN116154153A

  • Sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN116613288A

  • Composite sodium ion battery positive electrode material and preparation method thereof

    CN117913245A

  • Sodium supplementing material, positive electrode and sodium ion battery

    CN118335922A

Cited By

  • Preparation method of carbon-coated modified sodium ferric sulfate positive electrode material

    CN122889682A